Exposure to female estrous is beneficial for male mice against transient ischemic stroke. (3rd June 2019) - Qiao, Yuan; Ma, Qing; Zhai, Haifeng; Li, Ya; Tang, Minke
ABSTRACT: Objective : Exposure to female estrous, a natural rewarding experience, alleviates anxiety and depression, and the contribution of this behavior to stroke outcome is unknown. The aim of this study was to evaluate whether exposure to female estrous is beneficial to recovery following transient ischemic stroke in male mice. Methods : Cerebral ischemia was induced in male ICR mice with thread occlusion of the middle cerebral artery (MCAO) for 30 min followed by reperfusion. MCAO mice were randomly divided into MCAO group and Estrous Female Exposure (EFE) group. The mice in the EFE group were subjected to estrous female mouse interaction from day 1 until the end of the experiment. Mortality was recorded during the investigation. Behavioral functions were assessed by a beam-walking test and corner test from day 1 to day 10 after MCAO. Serum testosterone levels were analyzed with ELISA, and the expression levels of growth-associated protein-43 (GAP-43) and synaptophysin in the cortex of the ischemic hemisphere were determined by western blot on day 7 after MCAO. Results : Exposure to female estrous reduced the mortality induced by cerebral ischemic lesions. The beam-walking test demonstrated that exposure to female estrous significantly improved motor function recovery. The serum testosterone levels and ischemic cortex GAP-43 expression were significantly higher in MCAO male mice exposed to female estrous. Conclusion : Exposure to female estrous reduces mortality and improves functional recovery in MCAO male mice. The study provides the first evidence to support the importance of female interaction to male stroke rehabilitation. Abbreviations : GAP-43: growth-associated protein-43; SYP: Synaptophysin; MCAO: middle cerebral artery occlusion; OVXs: ovariectomies; CCA: common carotid artery; ECA: external carotid artery; EFE: estrous female exposure; TTC: 2, 3, 5-triphenyltetrazolium chloride; PAGE: polyacrylamide gel electrophoresis; PVDF: polyvinylidene difluoride; ANOVA: analysis of variance; LSD: least significant difference